2021
DOI: 10.3390/ijms22094525
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Silencing of Genes Coding for dTip60 Chromatin Remodeling Complex Subunits Affects Polytene Chromosome Organization and Proper Development in Drosophila melanogaster

Abstract: Chromatin organization is developmentally regulated by epigenetic changes mediated by histone-modifying enzymes and chromatin remodeling complexes. In Drosophila melanogaster, the Tip60 chromatin remodeling complex (dTip60) play roles in chromatin regulation, which are shared by evolutionarily-related complexes identified in animal and plants. Recently, it was found that most subunits previously assigned to the dTip60 complex are shared by two related complexes, DOM-A.C and DOM-B.C, defined by DOM-A and DOM-B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The unique Drosophila H2A variant, H2Av, combines the features of the H2A.X and H2A.Z eukaryotic variants and has been linked to transcription, DNA repair, and heterochromatin [ 36 ]. H2Av may also have a role in chromosome organization, since the depletion of the machinery responsible for its incorporation results in the alteration of chromosome structure in salivary glands and S2 cells [ 37 , 38 ]. H2Av is broadly distributed in the Drosophila genome and nucleosomes with H2Av are particularly enriched downstream of the transcription start site (TSS) of active genes, which correlates positively with transcription levels [ 25 , 39 ].…”
Section: Chromatin Composition and Structurementioning
confidence: 99%
“…The unique Drosophila H2A variant, H2Av, combines the features of the H2A.X and H2A.Z eukaryotic variants and has been linked to transcription, DNA repair, and heterochromatin [ 36 ]. H2Av may also have a role in chromosome organization, since the depletion of the machinery responsible for its incorporation results in the alteration of chromosome structure in salivary glands and S2 cells [ 37 , 38 ]. H2Av is broadly distributed in the Drosophila genome and nucleosomes with H2Av are particularly enriched downstream of the transcription start site (TSS) of active genes, which correlates positively with transcription levels [ 25 , 39 ].…”
Section: Chromatin Composition and Structurementioning
confidence: 99%
“…The F1 progeny of these crosses was analysed for chromosome segregation and chromatin integrity. The efficiency of RNAi constructs was already checked by semi-quantitative PCR [4]. Following RNAimediated depletion of the subunits under investigation induced in testes, we found chromatin integrity defects (CID) including condensation and chromosome segregation issues with loss of chromatin fragments (Figure 3 A,B and Table 1).…”
Section: Rnai Depletion Of Dom/tip60 Complex Subunitsmentioning
confidence: 94%
“…In past studies, we found that the lack of D. melanogaster YETI protein affects chromosome organization and impairs cytokinesis [42][43][44][45][46]. YETI is the Drosophila ortholog of CFDP1 [47][48][49] and belongs to the dTip60 chromatin remodeling complex [50] which includes subunits sharing high sequence and function conservation with those of SRCAP and p400/Tip60 complexes.…”
Section: Subcellular Localization and Rnai-mediated Depletion Of Mrg1...mentioning
confidence: 99%